2014
DOI: 10.1038/bjc.2014.500
|View full text |Cite
|
Sign up to set email alerts
|

SERPINE1 and SMA expression at the invasive front predict extracapsular spread and survival in oral squamous cell carcinoma

Abstract: Background:Extracapsular spread (ECS) in cervical lymph nodes is the single-most prognostic clinical variable in oral squamous cell carcinoma (OSCC), but diagnosis is possible only after histopathological examination. A promising biomarker in the primary tumour, alpha smooth muscle actin (SMA) has been shown to be highly prognostic, however, validated biomarkers to predict ECS prior to primary treatment are not yet available.Methods:In 102 OSCC cases, conventional imaging was compared with pTNM staging. SERPIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 65 publications
3
54
3
Order By: Relevance
“…Meanwhile, we found that Ki67 LI was significantly higher in high grade MPNSTs than that in low grade ones, probably suggesting that Ki67 could help distinguish between high and low grade MPNSTs. Both SMA and CD57 were confirmed to be the prognostic factors in some other tumors [33][34][35] but rarely reported in MPNSTs. We confirmed that both SMA and CD57 were not independent factors for postoperative recurrence and overall survival.…”
Section: Discussionmentioning
confidence: 86%
“…Meanwhile, we found that Ki67 LI was significantly higher in high grade MPNSTs than that in low grade ones, probably suggesting that Ki67 could help distinguish between high and low grade MPNSTs. Both SMA and CD57 were confirmed to be the prognostic factors in some other tumors [33][34][35] but rarely reported in MPNSTs. We confirmed that both SMA and CD57 were not independent factors for postoperative recurrence and overall survival.…”
Section: Discussionmentioning
confidence: 86%
“…After title/abstract screening, 20 text articles were subjected for full‐text evaluation, out of which nine were excluded for the following reasons: cases of OSCC not limited to the oral cavity (Parajuli et al, ), no Kaplan–Meier survival plots (Fonseca et al, ; Kellermann et al, , ; Lim et al, ; Vered, Dayan, et al, ; Zhou et al, ), immunohistochemical staining for the identification of CAFs other than α‐SMA (Inoue et al, ), and missing data (i.e., CAF density, mean age of patients and gender classification) (Inoue et al, ; Sobral et al, ). Finally, 11 articles were included in the meta‐analysis (Bae et al, ; Bello et al, ; Dayan et al, ; Dhanda et al, ; Ding et al, ; Fujii et al, ; Kawashiri et al, ; Li et al, ; Marsh et al, ; Matsuoka et al, ; Vered, Dobriyan, et al, ) (Table ; Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Possible mechanisms by which SERPINE1 contributes to cancer dissemination include the prevention of excessive degradation of the extracellular matrix, modulation of cell adhesion, and stimulation of angiogenesis and cell proliferation [38][39][40]. Immunohistochemical analysis revealed that both SERPINE1 and α-SMA at the tumor-advancing front of OSCCs were significantly associated with extracapsular spread of cervical lymph nodes, a prognostic marker of OSCC outcome, and the combination of α-SMA/SERPINE1 positivity was significantly associated with poor survival of OSCC patients [41]. Interestingly, C-188-9, a STAT-3 inhibitor, decreased pulmonary fibrosis and resulted in inhibition of fibroblast-to-myofibroblast differentiation and TGF-β-induced expression of multiple genes including SERPINE1 [42].…”
Section: Discussionmentioning
confidence: 99%